Monitoring sexual hormones in women going to high altitude—a pilot study - Taalaibekova, Aijan; Meyer, Michelle; Ulrich, Stefanie; Mirzalieva, Gulzada; Mademilov, Maamed; Lichtblau, Mona; Betschart, Cornelia; Sooronbaev, Talant M.; Ulrich, Silvia; Bloch, Konrad E.; Furian, Michael (Frontiers in Global Women's Health, 2025)
BackgroundThe susceptibility to acute mountain sickness (AMS) in relation to sexual hormones in women remains elusive, partly because hormones could not be conveniently measured. We evaluated a novel kit for self-monitoring sexual hormones in women and recorded AMS incidence during high-altitude sojourns.MethodsTwo groups of healthy, premenopausal women, mean ± SD age 23.1 ± 2.3 years, residing <1,000 m underwent baseline evaluations at 760 m before travelling to and staying for 2 days and nights (48 h) at 3,100 m or 3,600 m, respectively. Participants self-monitored morning urine sexual hormone concentrations (estrone-1-glucuronide, E1G, pregnanediol-3-alpha-glucuronide, PdG, and luteinizing hormone, LH) daily for 30d including altitude sojourns using the simple “Proov” kit (MFB Fertility Inc). Follicular and luteal menstrual cycle phases detected by LH peak, altitude-related adverse health effects (ARAHE), AMS [Lake Louise score 2018 (LLS) ≥ 3 points including headache] and pulse oximetry (SpO2) were assessed.Results1,172 of 1,250 (93.8%) hormone measurements were successful, 78 of 1,250 (6.2%) failed due to nonadherence or technical failure. At 3,600 m, mean differences in urinary PdG concentration were 3.8 mcg/ml (95% CI, 0.6–7.1) between luteal and follicular cycle phases. At 3,100 m, corresponding difference was 8.5 mcg/ml (95% CI, 5.0–12.0). At 3,100 m, 9 of 21 (43%) women were diagnosed with AMS with SpO2 of 93.0 ± 1.6% and LLS of 0.3 ± 1.4 in the morning after the first night. At 3,600 m, 12 of 21 (57%) women had AMS (p = 0.355 vs. 3,100 m) with SpO2 of 86.8 ± 1.8% (p < 0.05 vs. 3,100 m) and LLS of 1.9 ± 1.4 (p < 0.05 vs. 3,100 m).ConclusionSelf-monitoring female sexual hormones during high-altitude field studies with the employed kit is feasible and provides physiologically plausible trends of hormone levels over the menstrual cycle. Our data provide a valuable basis for designing further studies to evaluate AMS susceptibility in women.